Marketing Strategies for SMEs to Boost Sales of Moringa Leaf Sticks in Air Kering Village - Angga Trio Febriansyah; Nurzam Nurzam; Iswidana Utama Putra; Kenny Steward Putra (Utami Publisher, 2026)
The rapid growth of the culinary business sector has led to an increasing interest among the community in establishing food-based enterprises. This condition has encouraged the development of the Moringa Leaf Stick product business in Air Kering Village. This business operates in the culinary sector with a focus on producing snack foods in the form of moringa leaf sticks, which have nutritional value and competitiveness as healthy snacks. The development of this business is driven by the fulfillment of basic human needs for food as well as market opportunities for processed products based on natural and local ingredients.The purpose of this study is to identify and analyze the marketing strategy of the Moringa Leaf Stick product in Air Kering Village. The analytical method used is an analysis of internal and external factors, which are then mapped into a SWOT Matrix. The number of samples in this study was 45 respondents, consisting of 10 internal respondents and 35 external respondents.The results of the SWOT analysis show that the highest value is in the S–O (Strength–Opportunity) quadrant with a score of 6.72. This value was obtained from the calculation of strength and opportunity scores, indicating that the Moringa Leaf Stick business is able to maximize its internal strengths by taking advantage of existing external opportunities. Based on these results, the marketing strategy position of the Moringa Leaf Stick product in Air Kering Village is in Quadrant I, which means that the appropriate strategy to be implemented is the S–O strategy (supporting a growth strategy), where the business is in a strong condition and has significant opportunities to develop sustainably.